2018
DOI: 10.1002/clc.23110
|View full text |Cite
|
Sign up to set email alerts
|

Platelet inhibition to target reperfusion injury trial: Rationale and study design

Abstract: Background: In ST-segment elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (PPCI), current oral P2Y12 platelet inhibitors do not provide maximal platelet inhibition at the time of reperfusion. Furthermore, administration of cangrelor prior to reperfusion has been shown in pre-clinical studies to reduce myocardial infarct (MI) size. Therefore, we hypothesize that cangrelor administered prior to reperfusion in STEMI patients will reduce the incidence of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…A significant reduction in infarct size was also reported in monkeys when treated with cangrelor 100 . The current Platelet Inhibition to Target Reperfusion Injury (PITRI) trial aims to assess whether cangrelor administered prior to reperfusion will reduce AMI size as well as microvascular obstruction in STEMI patients treated with primary PCI 101 . In a retrospective analysis by Roubille et al 102 including 88 STEMI patients, clopidogrel treatment resulted in a reduction in final infarct size as assessed by cardiac enzyme release.…”
Section: Current and Future Therapeutic Interventions To Prevent Imentioning
confidence: 99%
“…A significant reduction in infarct size was also reported in monkeys when treated with cangrelor 100 . The current Platelet Inhibition to Target Reperfusion Injury (PITRI) trial aims to assess whether cangrelor administered prior to reperfusion will reduce AMI size as well as microvascular obstruction in STEMI patients treated with primary PCI 101 . In a retrospective analysis by Roubille et al 102 including 88 STEMI patients, clopidogrel treatment resulted in a reduction in final infarct size as assessed by cardiac enzyme release.…”
Section: Current and Future Therapeutic Interventions To Prevent Imentioning
confidence: 99%
“…The REDUCE-MVI trial [ 91 ] of 110 STEMI patients found no difference between ticagrelor and prasugrel in reducing MVO or infarct size, as assessed by invasive IMR evaluation and CMR at one month. The ongoing PITRI trial will aim to determine whether intravenous cangrelor administered prior to reperfusion reduces infarct size or MVO as assessed by CMR [ 92 ].…”
Section: Therapeutic Approaches In Mvomentioning
confidence: 99%
“…[ 72 ] The Platelet Inhibition to Target Reperfusion Injury (PITRI) trial is currently ongoing, and is evaluating whether cangrelor administered prior to reperfusion would reduce reperfusion injury, as assessed by CMR in 210 patients (NCT03102723). [ 73 ]…”
Section: Alternative Targets For Cardioprotectionmentioning
confidence: 99%